Waste Reduction with Lean Manufacturing Model in an Alpaca Wool Workshop - Cristobal Quispe, Jazmin Magaly (2020)
This paper proposes the design of a quasi-experimental time-series model comprising lean manufacturing tools—such as the value stream mapping and 5S's—with the aim of reducing the level of waste and losses in a micro-company dedicated to the production of Alpaca wool clothing in Junín, Perú. The model implementation managed to reduce the level of waste by 7%, increase the efficiency in material consumption, and reduce the cycle time and total supply time. The implementation of the model allowed reducing the level of waste in the production process and creating an organizational culture based on order, cleanliness, discipline, and teamwork.